1983
DOI: 10.1002/j.1460-2075.1983.tb01403.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro premature termination in SV40 late transcription.

Abstract: Nuclear extracts and viral transcribing minichromosomes were prepared from SV40‐infected cells and incubated in vitro with [alpha‐32P]UTP under conditions which allow the elongation of preinitiated RNA chains. Sucrose gradient lysis of the transcription mixtures revealed two populations of SV40‐specific RNA: elongating chains that remain associated with the viral minichromosomes, and, at the top of the gradient, small free RNA detached from the template and hybridizing exclusively to the promoter‐proximal regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1983
1983
1991
1991

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Furthermore, some Burkitt's lymphoma cell lines that have deregulated c-myc gene expression also have a concentration of mutations in the first exon and intron that correlate with abrogation of the transcriptional block (8). Similar intragenic transcriptional blocks have been observed in the human histone H3.3 gene (46), the human immunoglobulin ,u heavy-chain gene (19,35), the murine c-myc gene (40), the murine c-myb gene (2), the hamster c-fos gene (17), the Drosophila hsp70 gene (21), the simian virus 40 late region (23,24,25,42), the adenovirus major late transcription unit (16,18,33,39,41), and the human immunodeficiency virus type 1 long terminal repeat (31). Modulation of transcription elongation and termination is therefore a general mechanism for the regulation of gene expression in eucaryotic organisms.…”
mentioning
confidence: 64%
“…Furthermore, some Burkitt's lymphoma cell lines that have deregulated c-myc gene expression also have a concentration of mutations in the first exon and intron that correlate with abrogation of the transcriptional block (8). Similar intragenic transcriptional blocks have been observed in the human histone H3.3 gene (46), the human immunoglobulin ,u heavy-chain gene (19,35), the murine c-myc gene (40), the murine c-myb gene (2), the hamster c-fos gene (17), the Drosophila hsp70 gene (21), the simian virus 40 late region (23,24,25,42), the adenovirus major late transcription unit (16,18,33,39,41), and the human immunodeficiency virus type 1 long terminal repeat (31). Modulation of transcription elongation and termination is therefore a general mechanism for the regulation of gene expression in eucaryotic organisms.…”
mentioning
confidence: 64%
“…We have recently shown that pulse-labeling with (a-32P) UTP of SV40 transcriptional complexes (VTC), viral minichromosomes, nuclear matrices or isolated nuclei of SV40-infected cells leads to the production of 94-98 nt attenuator RNA (10,11,(16)(17)(18). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a series of studies with simian virus 40 (SV40) as the experimental system, it has recently been demonstrated that the eucaryotic polymerase B that transcribes SV40 RNA can respond to transcription termination and pausing signals similar to those of the procaryotic polymerase (31,55,56) and that a mechanism resembling attenuation in procaryotes regulates late transcription in SV40 (2,3,31,37,45,55,56). Moreover, a model in which attenuation and modulation of mRNA secondary structure in a feedback control mechanism quantitatively regulate SV40 gene expression has been presented (2,31).…”
mentioning
confidence: 99%